A reestruturação dos municípios sergipanos com base na sua viabilidade financeira - Melo, André Luis Dantas (2015)
This study analyzes the financial viability of municipalities in Sergipe. With the Federal Constitution of 1988, Brazil went through a fiscal decentralization and the municipalities increased their participation in tax collections. These increases have not guaranteed improvements in public services provided to the population. The objective of this paper is to see which municipalities do not have financial viability to remain independent. Five criteria were adopted to verify the feasibility of the municipalities: minimum number of inhabitants, number of existing homes, positive balance on the difference between revenues and expenditures, tax effort and the centrality of the municipality. The idea of annexations of municipalities comes at a time when the municipal administrators complain about the financial crisis affecting their economies and the pressure on the Federal Government to increase the transfers made, such as the Municipal Participation Fund or renegotiate existing debts. With annexations, it would be possible to invest more resources in areas that directly affect the local population, such as health and education. Besides the saving produced with the Executive Branch, these annexations would also cause a reduction in the number of legislative chambers, which in Brazil are often at the services of the Head of the Executive Branch. This would generate savings in 2010 alone, an amount of R$ 69,076,861.89. After the annexation, there would be a reduction in the number of municipalities in Sergipe, from the current 75 municipalities, the state would have only 27. The result of this analysis demonstrates the significant amounts that could be applied in the improvement of services to the local population and presenting, as an important point, no need for an increase in municipal public expenditure or increase in transfers from the federal and state governments.